Pengaruh Attraction, Accessibillity, Amenity, Ancillary Terhadap Kepuasan Generasi Millenial Berkunjung ke Tempat Wisata - Stella Alvianna; Ryan Gerry Patalo; Syarif Hidayatullah; Ike Kusdyah Rachmawati (Research and Community Service Center, Politeknik Pariwisata NHI Bandung, 2020)
Indonesia has various regions with potential tourism attractions that can attract tourists, one of them is Malang City, where Malang City is also known as one of the main tourist destinations in Indonesia. This study illustrates the influence of the components of tourism products consisting of attractions, access, amenities and ancillary to the decision of visiting tourists, especially millennial generation in the Tlogowaru mask tourism village of Malang. Topeng Village which is one of the tourist destinations in the form of thematic villages with the theme of Malangan Mask that has been around since the year 2016. The population of this study is all students of the Unmer Tourism Tourism Program Malang who entered the millennial age (aged between 15-34 years) with a sample of 60 people based on their characteristics visited Malangan mask village. Data analysis used multiple linear regression and hypothesis testing. The results of the research show that attraction and ancillary have a positive and significant effect on customer satisfaction. This shows the perception of what tourists get and what tourists feel can have a positive impact and also the presence of officers on guard, the presence of security posts and the existence of a tourist information center that continues to be maintained and improved, also has a positive impact on tourist attractions.